Inhibitors of nuclear factor kappa B cause apoptosis in cultured macrophages - E. E. Mannick; J. Mishra; J. Marque; M. Clavell; M. J. S. Miller; P. D. Oliver (Mediators of Inflammation)
The precise role of the transcription factor nuclear factor kappa B (NF- κB) in the regulation of cell survival and cell death is still unresolved and may depend on cell type and position in the cell cycle. The aim of this study was to determine if three pharmacologic inhibitors of NF-κB, pyrrolidine dithiocarbamate, N-tosyl-L-lysl chloromethyl ketone and calpain I inhibitor, induce apoptosis in a murine macrophage cell line (RAW 264.7) at doses similar to those required for NF-κB inhibition. We found that each of the three inhibitors resulted in a dose- and time-dependent increase in morphologic indices of apoptosis in unstimulated, LPS-stimulated and TNF-stimulated cells. Lethal doses were consistent with those required for NF- κB inhibition. We conclude that nuclear NF-κB activation may represent an important survival mechanism in macrophages.